POLÍTICA HABITACIONAL E (1M) PERMANENCIA DE FAMÍUAS REMANEJADAS: esludo sobre o projelo de urbanizacáo Vila da Barca em Belém, Pará - Alessandra Kelma de Souza; Joana Valente Santa na (Revista de Políticas Públicas, 2013)
The article presents an reflection regarding the present direction of Brazilian housing policy with respect lo ínlervention ín areas 01 precaríous settlemenls, where lhe inhabltants are not removed ín a way lo garanlee their permanence on those infra structured places. Highlights that since the Urbanization Project for the neighborhood Vila da Barca, in the city of Belém, the research aimed to verify in what extent this current direction effectively guarantee that the dislocated inhabitants could conitnue living in the housing project. Based on a marxist theoretical approach, the field research shows a contradictlon wílh respecl lo whal lhe governmenl claims ín íls díscourse. The removal 01famílles Irom precaríous settlemenls lo housinq projscts desarticulated the survíval strateqles 01 lhese famllles, creating obstacles lo lhe paymenl 01lhe urban servíces ín their new homes. Concludes that alter lhe relocation process lhere is a tendency lar lhem to sell their new homes, which reveals the impermanence question of the families after the relocation.